An electrochemical detection platform for selective and sensitive voltammetric determination of quercetin dosage in a food supplement by poly(9-(2-(pyren-1-yl)ethyl)-9h-carbazole) coated indium tin oxide electrode. (6th January 2021) - Karakaya, Serkan; Kaya, İsmet
Abstract: In proposed study, a novel compound containing carbazole (Carb) and pyrene (Pyr) units was synthesized and polymerized onto an indium tin oxide (ITO) electrode for selective and sensitive voltammetric determination of Quercetin (QCT). The characterization studies of the synthesized 9-(2-(pyren-1-yl) ethyl)-9H-carbazole (Pyr-Carb) were performed by NMR, LC-MS/MS, UV–Vis, Fluorescence and FT-IR measurements. Then, Pyr-Carb was electro-polymerized onto ITO by recording its cyclic voltammograms (CVs). Electro-oxidation behavior of QCT was investigated at bare ITO and poly (Pyr-Carb)/ITO by cyclic voltammetry (CV). The voltammetric measurements showed that the oxidation current of QCT significantly increased after electro polymerization of Pyr-Carb on the ITO surface. The range of linearity (ROL) and detection limit (DL) were found as 2.0–500 μM and 0.59 μM, respectively. The fabricated sensor was successfully tested on a Quercetin food supplement, and the obtained results indicated that the fabricated method enables sensitive, selective and accurate determination of QCT in real samples. Graphical abstract: Image 1 Highlights: A compound containing carbazole and pyrene units was electro polymerized on ITO. The characterization of the new compound was performed by spectral measurements. The voltammetric response significantly increased after electro polymerization. The sensor enables sensitive and accurate determination of QCT in real samples.